Investigation on wall thinning and creep damage in boiler tube due to scale formation - Begum, Shahida; Karim, A.N. Mustafizul; Shafi, M. A. (Trans Tech Publications Ltd., Switzerland, 2012)
Boiler is a closed vessel in which the water is heated up to convert it from the liquid phase to superheat steam at specified pressure by addition of heat. The tubes are operated continuously at high temperature due to the formation of scale which has lower conductivity than that of steel. The scale can be formed for various reasons of which tube geometries, flue gas and steam temperature are prominent. The remaining wall thickness decreases due to the formation of scale which eventually causes failure of the boiler tubes. In this investigation an iterative technique was used to determine the temperature distribution across the tube with the increase of operating time. The operating time was considered up to 160,000 hours. The remaining life of the steam generator tube was found by finding hoop stress and Larson Miller Parameter from the Larson Miller Parameter curve for SA213-T22 material. The remaining life of the steam generator tube was used to find cumulative creep damage. By utilizing finite element modelling software, ANSYS 9/ ANSYS 11 the temperature distribution across the steam generator tube was evaluated. The temperature distribution along with Larson Miller Parameter predicted the oxide scale thickness. It was also observed that different input parameters have pronounced affect on the formation of oxide scale inside the steam generator tube. By increasing the heat transfer rate across the wall, the oxide scale thickness was increased more rapidly than normal condition. It was also observed that due to formation of scale the thermal conductivity in the boiler tubes was affected and the remaining life of boiler tubes was decreased and accelerated creep damage.